Risk factors associated with eating disorders in adolescents from Metropolitan Lima - Riveros-Arenas, Giomy (2025)
The aim of this study was to determine the risk factors that predict the presence of symptoms of Eating Disorders (ED) in a group of 218 female adolescents between the ages of 12 and 18 years (M = 15, SD = 1.33), all of them students of a public educational institution in Metropolitan Lima. For this purpose, two measurement tools were used: Eating Attitudes Test (EAT-26) and Eating Disorder Inventory (EDI-3). For the predictive analysis, a multiple linear regression analysis and a correlational analysis were performed through the Shapiro Wilk test, where it was found that there are 3 factors that predict future ED to a greater extent, within these are the Obsession with thinness (DT), Bulimic behaviors (B) and Asceticism (AS), while those that predict to a lesser extent the appearance of the condition are Fear of maturity (FM) and Emotional maladjustment (EM). These factors are related to characteristics specific to the developmental age of adolescents and the challenges they face at a social and personal level during this stage.